Perfluorooctanoic acid (PFOA) but not perfluorooctane sulfonate (PFOS) showed DNA damage in comet assay on Paramecium caudatum - Kawamoto, Kosuke; Oashi, Takahiro; Oami, Kazunori; Liu, Wei; Jin, Yihe; Saito, Norimitsu; Sato, Itaru; Tsuda, Shuji (Journal of toxicological sciences, 2010)
Persistent perfluorinated organic compounds such as perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA) are distributed widely in the global environment including wildlife and human. In this study, we investigated the genotoxicity of PFOS and PFOA using the novel in vivo comet assay developed for Paramecium caudatum. For the comet assay, large nuclei squeezed out of the paramecia with 0.25 M sucrose containing 0.6% Triton X-100 were embedded in a layer of agarose gel placed over the slide glass. N-methyl-N´-nitro-N-nitrosoguanidine (MNNG) and 2-aminoanthracene (2-AA) were successfully used for positive controls. Productions of 8-hydroxydeoxyguanosine (8-OH-dG) and intracellular reactive oxygen species (ROS) were also measured in paramecia. PFOS did not cause DNA damage on any conditions examined. On the other hand, 12 and 24 hr exposure to PFOA (100 µM) increased DNA migration in electrophoresis condition at pH 13, but not at pH 12.1, suggesting that the DNA damage may be alkali labile site (such as apurinic/apyrimidinic (AP) site). Exposure of paramecia to 100 µM PFOA for 1, 3 and 24 hr and to 10 µM PFOA for 24 hr significantly increased intracellular ROS. Under the same condition, however, 8-OH-dG level was not affected by PFOA. The PFOA-induced DNA damage was not abolished by the application of 100 µM GSH which completely inhibited the increase of intracellular ROS. In conclusion, the PFOA-induced in vivo DNA damage was first shown in paramecia, and the DNA damage might not be directly attributable to increase in intracellular ROS.